2022
DOI: 10.4103/sujhs.sujhs_17_22
|View full text |Cite
|
Sign up to set email alerts
|

Ocular trauma

Abstract: Background: According to the WHO, ocular injury results in 19 million people to become unilateral blind and 1.6 million to become bilateral blind. Ocular trauma constitutes a major part of preventable blindness. The following study was done to identify the demographic profile of the patients and nature of ocular trauma for developing acceptable methods for better management and early visual rehabilitation of patients. Aim: The aim was to study various d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…of trauma, this was due to the fact that protective eyewear is less common among people especially those working at home. (9,12,13) To sum up, in this hospital based study, Closed globe injury was the most common types of injuries occurred between the age of 30-40 and male were most commonly susceptible. Most of the injuries are preventable which re ect the importance of using protective equipment and better awareness to lesson ocular traumas.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…of trauma, this was due to the fact that protective eyewear is less common among people especially those working at home. (9,12,13) To sum up, in this hospital based study, Closed globe injury was the most common types of injuries occurred between the age of 30-40 and male were most commonly susceptible. Most of the injuries are preventable which re ect the importance of using protective equipment and better awareness to lesson ocular traumas.…”
Section: Discussionmentioning
confidence: 79%
“…Pawaiya S et al reported 72 (43.6%) patients were affected in the right eye 84 (50.9%) in the left eye, and only nine patients had bilateral trauma. Wanpeng Wang also showed that (48.5%) of patients had trauma in their right eye and (49.4%) in the left eye, bilateral trauma was almost (2.1%) (9,14). Dr. Kalpana Singh et al, found that open and closed globe injuries were the most prevalent types of traumas at 48% and 49% respectively, Ekta Syal also reported that 60.5% of traumas were Closed globe injuries in consistent with our results in which conjunctiva foreign body was the common types of traumas at about 36.7%.…”
mentioning
confidence: 93%